Geoscience Education Indoor and Outdoor - Vasconcelos, Clara (Springer International Publishing : Imprint: Springer, 2016)
This book presents research in Geoscience Education focusing on indoor and outdoor environments in which teaching geoscience gains particular relevance, significance and contextualization. The research areas that are presented throughout the thirteen chapters cover a wide variety of subjects ranging from educational resources and fieldwork to science models. Chapters discuss specific geoscience topics such as earthquakes, rocks, fossils and minerals. Other chapters present a more interdisciplinary approach addressing topics that aren't usually examined, such as geomedicine and geoethics, with a specific focus on sustainable development and their alignment with the school curricula. Throughout the book readers can find research-based arguments illustrated with practical examples, which will help them to innovate in their curriculum development area, classroom practices and pre and in-service teachers' education. The book challenges readers to improve Geoscience Education by changing the ways of teaching, by enabling students to exploit their natural curiosity, and by spurring a learning process that should not be confined to the classroom but rather maintained throughout life. .